A comment on "An arbitrage-free approach to quasi-option value" by Coggins and Ramezani - Paul Mensink (Kiel University, Department of Economics, 2004)
In their article "An Arbitrage-Free Approach to Quasi-Option Value" [J. Environm. Econom. Management 35, 103-125, 1998], Coggins and Ramezani interpreted the concept of quasi-option value introduced by Arrow and Fisher [Quart. J. Econom. 88, 1974, 312-319] as being identical to Dixit and Pindyck's real option value. This means their approach differs from the approach by Fisher and Hanemann [J. Environm. Econom. Management 14, 183-190, 1987] who formalized the concept of quasi-option value a decade before. By indirectly characterizing Dixit and Pindyck's real option value Coggins and Ramezani confirmed classic results in the field of real options theory.
Keywords: 330; Realoption; Optionspreistheorie; Theorie